82.7k views
5 votes
Given the functions k(x) = 2x2 − 7 and p(x) = x − 4, find (k ∘ p)(x). (k ∘ p)(x) = 2x2 − 8x + 16 (k ∘ p)(x) = 2x2 − 16x + 32 (k ∘ p)(x) = 2x2 − 16x + 25 (k ∘ p)(x) = 2x2 − 11

User Sdonk
by
4.2k points

2 Answers

5 votes

Answer:

(k ∘ p)(x) = 2x² - 16x + 25

Explanation:

hope this helps

User Abstract
by
4.0k points
5 votes

Answer:

(k ∘ p)(x) = 2x² - 16x + 25

Explanation:

k(x) = 2x² - 7

p(x) = x - 4

To find (k ∘ p)(x) substitute p(x) into k(x),

that's replace any x in k(x) by p(x)

We have

(k ∘ p)(x) = 2(x - 4)² - 7

Expand

(k ∘ p)(x) = 2( x² - 8x + 16) - 7

= 2x² - 16x + 32 - 7

Simplify

We have the final answer as

(k ∘ p)(x) = 2x² - 16x + 25

Hope this helps you

User Stefan Bollmann
by
5.1k points